2000
DOI: 10.1509/jppm.19.2.228.17127
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward Direct Marketing and its Regulation: A Comparison of the United States and Japan

Abstract: The authors propose that the high-context nature of Japanese communication and the collectivistic nature of Japanese culture have an impact on attitudes toward direct marketing and its regulation. The results of a survey of Japanese and U.S. university students suggest that certain types of direct marketing messages are less effective in Japan than in the United States. The results also indicate a greater willingness by Japanese respondents to support regulation of direct marketing practices. The authors discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Research into US pharmaceutical advertising has noted the difficulty of regulating direct marketing (Gibson, 2014; Henney, 2000; Mackey, 2016; Taylor, Franke, & Maynard, 2000). Gibson (2014) concluded that third party oversight and industry self-regulation are important in regulating direct marketing, although gambling industry self-regulation has been criticized (Selin, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Research into US pharmaceutical advertising has noted the difficulty of regulating direct marketing (Gibson, 2014; Henney, 2000; Mackey, 2016; Taylor, Franke, & Maynard, 2000). Gibson (2014) concluded that third party oversight and industry self-regulation are important in regulating direct marketing, although gambling industry self-regulation has been criticized (Selin, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Ferley, Lea and Watson (1999) found significant differences between Canadian and U.S. consumers in terms of product-usage patterns. Taylor, Franke and Maynard (2000) examined the behavior of Japanese consumers compared to U. S. consumers with regard to their attitudes toward telemarketing. Because Japan is a high-context country where relationships come before business, the Japanese consumers perceived the telemarketing calls from an unknown source as even more rude and intrusive than U. S. consumers did.…”
Section: The I Nfluence Of Culture On Consum Er Behavi Ormentioning
confidence: 99%
“…The effect of individualism-collectivism on risk perception is likely to be situation specific. Taylor et al (2000) noted that privacy in a collectivist culture is not important among in-group members since they are expected to share personal thoughts and feelings and trust one another. Weber and Hsee (1998) identified a cushion effect among Chinese who exhibit strong collectivism.…”
Section: Culture and Planned Behaviormentioning
confidence: 99%
“…Culture has also been found to affect how an individual responds to a potential risk (Taylor et al, 2000;Yamagishi & Yamagishi, 1994;Bontempo et al, 1997;Weber & Hsee, 1998). Individuals' cognitive propensity to risk differs across cultures and is likely to affect the perceptions of the presence of risks as well as the evaluation of the risks (Tse et al, 1988).…”
Section: Uncertainty Avoidance and Consumer Decision-makingmentioning
confidence: 99%